ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS MEREK PADA PRODUK HANDPHONE MEREK IPHONE DENGAN KEPUASAN PELANGGAN DAN KUALITAS PRODUK SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PENGGUNA IPHONE DI KOTA SEMARANG) - Sitanggang, Suci A Y; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2017)
This study animed to analyze factors that effect brand loyalty on iphone with the customer satisfaction and quality of products as intervening variables on the user’s phone brand the iphone yn the city of Semarang. The variables used in this study are service quality as independent variables, then the customer’s satisfaction and quality of product as intervening variables and brand loyalty as the dependent variable.Sample in this study are 158 respondents of iphone customer’s in Semarang. The method used is Accedental Sampling by distributting questionnaires to the respondents. The study developed a theoretical model with purposeto of examine four hyphotheses to be tested using analysis tools Structural Equation Modelling (SEM) which is operated through a program AMOS 22.0Based in research of data processing SEM full mdel has met the criteria of goodness of fit as follows: the value of chi-square, CMIN/DF, CFI, TLI, GFI, AGFI, probability, RMSEA. Within the result, it can be said that this model is feasible to be used. The result show that the brand loyalty can be improved by increasing quality of product affect the customer’s satisfaction as a determinant of success increase brand loyalty.